Peningkatan Kapasitas Inovasi UMKM Binaan Aisyiyah Pekanbaru melalui Pelatihan Persona Prompting Berbasis GenAI - Hartati, Seri; Arisandi, Diki; Mutiara, Destita; Suriyanti, Linda Hetri; Farras, Aqil (Journal of Community Sustainability, 2025)
Micro, Small, and Medium Enterprises (MSMEs) mentored by Aisyiyah Pekanbaru face challenges in product innovation and marketing strategies due to limited human resources, lack of optimal digital technology utilization, and insufficient understanding of consumer behavior. These issues weaken the competitiveness of MSMEs amid an accelerating digital transformation. This community engagement program aims to enhance the innovation capacity of MSME actors through training in persona prompting powered by Generative AI (GenAI), enabling participants to generate creative ideas and market-relevant content. The program implementation consisted of: (1) initial needs assessment and participant potential mapping; (2) an interactive workshop on persona development, prompt creation, and GenAI applications; (3) hands-on practice in crafting persona-based prompts for product and content development; and (4) a two-week post-training mentoring phase. A total of 25 MSME actors actively participated. Evaluation using pre-and post-tests showed a significant improvement in participants’ ability to create innovative prompts (with the average score rising from 58.1 to 84.3). Moreover, 72% of participants successfully produced at least one marketing content prototype based on GenAI output. These findings demonstrate that persona prompting training using GenAI is an effective and practical approach to fostering MSME innovation in a digital context.